STRATEGI PEMBINAAN AGAMA ISLAM PADA NARAPIDANA DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) kLAS II KABUPATEN MAMUJU (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal was created to describe "How the Strategy of Islamic Religious Development in Prisoners at the Special Child Development Institute (LPKA) Klas II Kabupaten Mamuju". The results of this study show that Efforts to foster Islam in prisoners at the Klas II Special Child Development Institute (LPKA) in Mamuju Regency are carried out using two methods, namely: individual guidance and group guidance where the implementation includes several materials, namely Reading iqro and Quranic Recitation Routine, Fiqh practice. There are two obstacles to coaching, namely the background factor of the prisoner's religious knowledge and the lack of religious guidance in LPKA. The implications of this study are: 1) It is hoped that the Special Child Development Institute (LPKA) Klas II Mamuju Regency can be more frequent in carrying out Islamic Agam coaching for Prisoners.2) The Ministry of Religion's Religious extension should continue to cooperate so that Islamic guidance remains optimal.3) Coaching activities to be better programmed.